Conceptualizing and Framing Economic Security?: The Case of 30 Year Russian–Korean Security Relations Tested - 안세현 (The Korean journal of defense analysis, 2021)
This article examines Korean–Russian relations from a new dimension of security, economic security. This is an important study of an understudied relationship in East Asia that has significant implications for the security, energy and other economic activities of the region. The objective of this article is to broaden the concept of security, conceptualize the notion of economic security and apply it to the case of bilateral relations between Moscow and Seoul. This article focuses on the securitization process of international political issues and security-building processes between two nations. Specifically, this study intends to specifically look at the following four aspects of security: nation states’ perceptions of security, securitization, the security-building process, and potential security threats. In this respect, the article begins by redefining the definition of security and economic security and applying their relevance to the Russian–South Korean bilateral relations. And then the article explores specific elements of economic security, including energy, transportation linkage, and fishery cooperation since these three elements represent core elements of economic security cooperation between two countries. KCI Citation Count: 2